Characterising and Addressing the Psychosocial Impact of Tuberculosis in Indonesia (CAPITA): A study protocol [version 2; peer review: 2 approved] - Tom Wingfield; Ahmad Fuady; Agus Sugiharto; Agus Fitriangga; Ferdiana Yunita; Bustanul Arifin; Saidah Rauf; Helmi Suryani Nasution; Finny Fitry Yani; Muchtaruddin Mansyur; I Wayan Gede Artawan Eka Putra (Wellcome Open Research, 2022)
Background: Tuberculosis (TB)-related stigma remains a key barrier for people with TB to access and engage with TB services and can contribute to the development of mental illnesses. This study aims to characterise stigmatisation towards people with TB and its psychosocial impact in Indonesia. Methods: This study will apply a sequential mixed method in two main settings: TB services-based population (setting 1) and workplace-based population (setting 2). In setting 1, we will interview 770 adults with TB who undergo sensitive-drug TB treatment in seven provinces of Indonesia. The interview will use the validated TB Stigma Scale questionnaire, Patient Health Questionnaire-9, and EQ-5D-5L to assess stigma, mental illness, and quality of life. In Setting 2, we will deploy an online questionnaire to 640 adult employees in 12 public and private companies. The quantitative data will be followed by in-depth interview to TB-related stakeholders. Results: CAPITA will not only characterise the enacted stigma which are directly experienced by people with TB, but also self-stigma felt by people with TB, secondary stigma faced by their family members, and structural stigma related to the law and policy. The qualitative analyses will strengthen the quantitative findings to formulate the potential policy direction for zero TB stigma in health service facilities and workplaces. Involving all stakeholders, i.e., people with TB, healthcare workers, National Tuberculosis Program officers, The Ministry of Health Workforce, company managers, and employees, will enhance the policy formulation. The validated tool to measure TB-related stigma will also be promoted for scaling up to be implemented at the national level. Conclusions: To improve patient-centered TB control strategy policy, it is essential to characterise and address TB-related stigma and mental illness and explore the needs for psychosocial support for an effective intervention to mitigate the psychosocial impact of TB.